Potensi Ekstrak Metanol Rhizom Alang-Alang (Imperata cylindrica (L.) (Beauv) ) Dalam Penghambatan Pertumbuhan Gulma Maman Ungu (Cleome rutidosperma D.C) - Riza Linda, Lucia Apri, Mukarlina (Jurnal Protobiont, 2018)
Purple Maman (Cleome rutidosperma) is a type of weed which lives in various places, especially in agricultural land and plantation. For example, they are frequently found in palm plantation. Cogon grass (Imperata cylindrical L.) is long grass plants spreading all over the word and perceived as weed for agricultural land as it contains allelochemical compounds. This research aims at identifying the effect of extract of rhizome methanol extract of cogon grass in inhibiting the growth of purple cleome. In addition, it is keen on examining the ideal concentration of rhizome methanol extract of cogon grass. The research was conducted for three months since May to July 2017. The research was carried out in the Laboratory and grass house of the biology department, faculty of mathematics and natural sciences. Futher, the sample was grinded in agronomic department, faculty of Agriculture. Finally, the macerate evaporation was conducted in the agricultural product Process lab, State Polytechnic of Pontianak. It used a completely randomized design (RAL) with four concentration treatments, covering control 0; 0.2; 0.3 and 0.4 g/ml. Each concentration was repeated three times until it collected 12 experiment units. Results show that rhizome methanol extract of cogon grass indeed inhibited the growth of the purple cleome, especially on the on 0.3 g/ml and 0.2 g/ml germination concentration.